Profil Kecerdasan Linguistik Mahasiswa Tingkat Akhir Dalam Menyusun Karya Ilmiah - Imaratul Ulwiyah; Nostalgianti Citra Prystiananta (Journal on Education, 2024)
Composing an article or a thesis is a must for the final semester students in the university. Unfortunately, not all of them could make it easily. Some of them are still having difficulties to find ideas and replace it to the written form based on the right grammar of Indonesian language. Therefore, this study has been done by knowing the linguistic’s profile of the students. Someone that has good linguistic profile should comply some criterion. This study uses qualitative method with purposive sampling. Then, the data obtained will be validated by informan review. There are 5 informans of this study and the result shows that one (1) student has high level of linguistic intelligence, 3 students are in the middle level and another one with the lowest level.